2016
DOI: 10.1590/0001-3765201620140635
|View full text |Cite
|
Sign up to set email alerts
|

Branching, flowering and fruiting of Jatropha curcas treated with ethephon or benzyladenine and gibberellins

Abstract: Jatropha curcas L. has been identifi ed for biofuel production but it presents limited commercial yields due to limited branching and a lack of yield uniformity. The objective of this study was to evaluate the effects of single application of ethephon or a combination of 6-benzyladenine (BA) with gibberellic acid isomers A 4 and A 7 (GA 4+7 ) on branch induction, fl owering and fruit production in jatropha plants with and without leaves. Plants with and without leaves showed differences for growth and reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
0
5
1
4
Order By: Relevance
“…Increase in the number of female and bisexual flowers has been indicated as an important strategy for increasing seed yield in J. curcas plants. In spite of positive reports regarding the use of growth regulators in the sexual expression of flowers (Brito et al, 2015;Costa et al, 2016), the present study reported no significance of the kinetin concentration on any of the variables analyzed. Very possibly the type of cytokinin applied (kinetin) was different from that used in other research (benzyladenine) (Pan et al, 2011;Matos et al, 2013) and played a fundamental role in the sexual expression.…”
Section: Introductioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Increase in the number of female and bisexual flowers has been indicated as an important strategy for increasing seed yield in J. curcas plants. In spite of positive reports regarding the use of growth regulators in the sexual expression of flowers (Brito et al, 2015;Costa et al, 2016), the present study reported no significance of the kinetin concentration on any of the variables analyzed. Very possibly the type of cytokinin applied (kinetin) was different from that used in other research (benzyladenine) (Pan et al, 2011;Matos et al, 2013) and played a fundamental role in the sexual expression.…”
Section: Introductioncontrasting
confidence: 98%
“…Increase in the female and/or bisexual flowers seems to be fundamental to improve yield. Recent research has indicated that applying growth regulators improved the yield of several species (Doorn et al, 2011;Greene et al, 2011;Purgatto and Colli, 2008;Cassiano et al, 2013;Muller et al, 2015;Costa et al, 2016). Matos et al (2013) showed that in Brazilian Cerrado (Savannah) region, the total number of male flowers produced by the inflorescences is always greater than the number of female flowers, resulting in low yield, so that increase in female and/or bisexual flowers seems to be essential to reach satisfactory J. curcas fruit yields.…”
Section: Introductionmentioning
confidence: 99%
“…No substantial changes in growth parameters were observed when explants were treated with cytokinin along with GA 3 and NAA. It is evident from others results that gibberellins did not enhance the shoot length [12]. These results suggest that GA 3 was slightly effective than NAA when used in synergy with BAP or Kin.…”
Section: Discussionmentioning
confidence: 61%
“…Fresnedo-Ramirez and Orozco-Ramirez (2013) has reported that flower sex ratio in JCL is genetically controlled and can be altered by photoperiod, relative humidity, temperature, soil nutrient availability, exogenously applied growth regulators and by an epigenetic control. Plant growth regulators such as benzyladenine and gibberellic acid could affect number of flowers and branching but would not modify the genetics (Costa et al, 2016). Also, some genes play a role in regulating flowering; the gene jcLFY in JLC regulates flower identity, flower organ patterns and fruit shape (Tang et al, 2016), JcTFL1 genes play redundant roles in repressing flowering in Jatropha (Li et al, 2017).…”
Section: Crossing Accession Naturally Expressing Fof Trait With Fm Acmentioning
confidence: 99%
“…Although there are studies on JLC flowering biology (Heller, 1996;Pecina-Quintero et al, 2011;Adriano-Anaya et al, 2016;Costa et al, 2016;Tang et al, 2016;Li et al, 2017), including a published patent WO2011084867 A2 (Rotter, 2010), little is known about the type of inheritance patterns of the FOF trait. The objective of this work was to elucidate the heredity of the FOF native trait through the inbreeding and crossing process of JCL accessions for further potential usage as female parent for commercial hybrid seed production.…”
Section: Introductionmentioning
confidence: 99%